Method for producing oxide single crystals by solvent-moving floating zone melting method and lithium cobalt oxide single crystals

The solvent-transfer floating zone melting method addresses the challenges of producing large-diameter lithium cobaltate single crystals by maintaining a stable melting zone with a higher metal content in the raw material rod, resulting in crystals exceeding 7 mm in diameter.

JP7662177B2Active Publication Date: 2025-04-15UNIVERSITY OF YAMANASHI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020216337
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-25
Publication Date
2025-04-15
Estimated Expiration
2040-12-25

AI Technical Summary

Technical Problem

Existing methods for producing large-diameter lithium cobaltate single crystals face challenges such as decomposition and severe lithium evaporation, limiting the achievable diameter to less than 7 mm.

Method used

A solvent-transfer floating zone melting method is employed, where a melting zone with a solvent of different composition forms between the raw material rod and the seed crystal, allowing for a higher content of the first metal element in the raw material rod compared to the single crystal, thereby maintaining a stable melting zone and achieving larger crystal diameters.

Benefits of technology

This method enables the growth of oxide single crystals with diameters over 7 mm and lithium cobaltate single crystals with diameters of 10 mm or more, overcoming the limitations of previous techniques.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662177000001
    Figure 0007662177000001
  • Figure 0007662177000002
    Figure 0007662177000002
  • Figure 0007662177000003
    Figure 0007662177000003
Patent Text Reader

Abstract

To provide a method of manufacturing single crystal that can rear oxide single crystal having a diameter of larger than 7 mm, and cobaltic acid lithium single crystal having a diameter of 10 mm or larger.SOLUTION: There is provided a method of manufacturing oxide single crystal by solvent movement / flotation zone melting method, and the method of manufacturing the oxide single crystal includes processes of forming a melting zone 4 including a solvent of different composition from a raw material rod between a raw material rod 1 and seed crystal 2, and growing oxide single crystal on the seed crystal 2, wherein the oxide single crystal includes at least a first metal element and a second metal element, the raw material rod 1 includes at least the first metal element and second metal element, the raw material rod has a larger content of the first metal element than the oxide single crystal. The first metal element is alkali metal, and the oxide single crystal has a diameter of 10 mm or larger and a thickness of 3 mm or larger, and includes at least Li and Co.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an oxide single crystal by a moving solvent floating zone melting method, and to a lithium cobalt oxide single crystal. [Background technology]

[0002] Many of the single crystal materials with large market share, such as silicon, sapphire, gallium arsenide, lithium niobate, lithium tantalate, and lithium tetraborate, are manufactured using methods such as the Czochralski (Cz) method, in which a seed crystal is brought into contact with the raw material melt in a crucible and pulled upward, and the Bridgman method, in which a crucible containing the raw material melt is moved to the low temperature side. The advantage of these methods is that they can mass-produce high-quality, large-diameter crystals. On the other hand, one of the disadvantages is that a crucible is required for crystal growth.

[0003] The floating zone (FZ) method is a method in which a part of a polycrystalline raw material rod is heated to create a molten zone between the raw material rod and a single crystal to be used as a seed crystal, and the molten zone is moved while being supported by surface tension, and the molten zone is cooled to obtain a single crystal. The FZ method is a manufacturing method that does not use a crucible, so it has the advantage of being able to avoid impurities from the crucible and to obtain a single crystal with high purity. In addition, the traveling solvent floating zone (TSFZ) method is an FZ method in which a solvent with a different composition from the composition of the raw material rod is used in the molten zone.

[0004] Meanwhile, in order to commercialize lithium cobalt oxide single crystal wafers that will be used as positive electrode material substrates for next-generation lithium-ion secondary batteries, there is an urgent need to establish technology for manufacturing large-diameter lithium cobalt oxide single crystals with a diameter of 1 / 2 inch or more at low cost. In addition, sodium cobaltate, which has attracted attention as a thermoelectric material, is known to have improved thermoelectric conversion properties when made into a single crystal, and there is a similar demand for the establishment of a technique for growing single crystals of this material.

[0005] Patent Document 1 discloses a bulk single crystal of a compound represented by chemical formula A x CoO2(0 < x ≤ 1, A = Li or Na), which is characterized in that the length, width, and height of the single crystal are each at least 1 mm or more. Patent Document 2 discloses A x heating CoO2 powder to a temperature above its melting point to melt it and then cooling it, characterized in that the length, width, and height of the single crystal are each at least 1 mm or more, and chemical A x A method for producing a bulk single crystal of a compound represented by CoO2(0 < x ≤ 1, A = Li or Na) is disclosed.

[0006] In addition, Non-Patent Documents 1 to 3 disclose bulk single crystals such as lithium cobaltate grown by the TSFZ method and a method for producing the same.

Prior Art Documents

Patent Documents

[0007]

Patent Document 1

Patent Document 2

Non-Patent Documents

[0008]

Non-Patent Document 1

Non-Patent Document 2

[0009] However, the methods for producing single crystals described in Patent Documents 1 and 2 were unable to produce large-diameter oxide single crystals. In addition, since the raw material needs to be melted at a temperature equal to or higher than the melting point, there are problems in that decomposition and melting occurs and Li evaporates rapidly. In addition, the lithium cobalt oxide single crystals disclosed in Non-Patent Documents 1 to 3 have a maximum diameter of 7 mm, and the disclosed production methods were unable to produce large-diameter lithium cobalt oxide single crystals with a diameter exceeding 7 mm.

[0010] The present invention has been made in view of the above circumstances, and provides a method for producing a single crystal capable of growing an oxide single crystal having a diameter exceeding 7 mm, which was difficult to achieve using conventional production methods, and a large-diameter lithium cobalt oxide single crystal having a diameter of 10 mm or more. [Means for solving the problem]

[0011] According to the present invention, there is provided a method for producing an oxide single crystal by a moving solvent floating zone melting method, comprising the steps of: A molten zone containing a solvent having a composition different from that of the feed rod is formed between the feed rod and the seed crystal, growing the oxide single crystal on the seed crystal; The oxide single crystal contains at least a first metal element and a second metal element, The raw material rod contains at least the first metal element and the second metal element, The present invention provides a method for producing an oxide single crystal, wherein the content of the first metal element in the raw material bar is greater than the content of the first metal element in the oxide single crystal.

[0012] After extensive research, the inventors discovered that in a method for producing an oxide single crystal containing at least a first metal element and a second metal element by a solvent moving floating zone melting method, by making the content of the first metal element contained not only in the solvent but also in the feed rod greater than the content of the first metal element in the oxide single crystal, it is possible to compensate for the metal element that evaporates during crystal growth, thereby making it possible to maintain a highly stable molten zone during crystal growth and to obtain a large-diameter, high-quality oxide single crystal, which led to the completion of the present invention.

[0013] Various embodiments of the present invention will be described below. The embodiments described below can be combined with each other. It is Noh. Preferably, the first metal element is an alkali metal. Preferably, the oxide constituting the oxide single crystal is a decomposed molten oxide. Preferably, the length of the molten zone is 5 mm or more. Preferably, the amount of the solvent is 2.0 g or more. Preferably, the content of the first metal element in the solvent is greater than the content of the first metal element in the raw material.

[0014] According to another aspect of the present invention, there is provided an oxide single crystal having a diameter of 10 mm or more and a thickness of 3 mm or more, said oxide single crystal containing at least Li and Co. [Brief description of the drawings]

[0015] [Figure 1] 1 is a schematic diagram of a crystal growth process using a TSFZ method according to one embodiment of the present invention; [Diagram 2] FIG. 1 shows a schematic diagram of a tilted mirror device according to one embodiment of the present invention. [Diagram 3] 1 shows a photograph of a heat lamp according to an experimental example. [Figure 4] This shows a photograph of a lithium cobalt oxide single crystal having a diameter of 10 mm, which was grown by changing the amount of Li in the feed rod according to an experimental example. [Diagram 5] This shows a photograph of a lithium cobalt oxide single crystal having a diameter of 13 mm, which was grown by changing the amount of Li in the feed rod according to an experimental example. [Figure 6] 1 shows an SEM photograph of a grown lithium cobalt oxide single crystal according to an experimental example. [Figure 7] The relationship between the amount of excess Li in the feed rod and the required lamp power is shown. [Figure 8] The relationship between the amount of excess Li in the feed rod, the diameter of the single crystal, and the required lamp power is shown. [Figure 9] The relationship between the diameter of the single crystal and the optimum amount of solvent is shown. [Figure 10] 1 shows a photograph of a molten zone during growth of a LiCoO2 single crystal having a diameter of 10 mm according to an experimental example. [Figure 11] 1 shows a schematic diagram of a light collection image according to an experimental example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be described in detail below by illustrating the embodiments of the present invention. The present invention is not limited by these descriptions. The various features of the embodiments of the present invention shown below can be combined with each other. In addition, each feature can be an invention independently.

[0017] The present invention relates to a method for producing oxide single crystals by a moving solvent floating zone melting method. The TSFZ method is a type of FZ method, in which a solvent with a different composition from that of a feed rod is placed between a feed rod and a seed crystal, the solvent is heated and melted to form a molten zone, and the molten zone is moved relative to the feed rod and the seed crystal while being supported by surface tension, so that the target single crystal grows on the seed crystal. The method for producing oxide single crystals by the moving solvent floating zone melting method according to the present invention will be described in detail below.

[0018] The manufacturing object of the manufacturing method according to the present invention is a single crystal of an oxide containing at least a first metal element and a second metal element. The oxide may contain, in addition to the first metal element and the second metal element, a metal element other than the first metal element and the second metal element. The raw material rod serving as the raw material of the oxide single crystal is an oxide containing at least the first metal element and the second metal element. The raw material rod may be a sintered body of an oxide containing at least the first metal element and the second metal element. The raw material rod may contain, in addition to the first metal element and the second metal element, a metal element other than the first metal element and the second metal element. The content of the first metal element in the raw material rod is higher than the content of the first metal element in the oxide single crystal. In the conventional TSFZ method, the composition of the raw material rod is usually adjusted to the composition of the oxide single crystal to be manufactured in order to obtain a single crystal having the composition of the target substance. That is, conventionally, raw material having the composition of the desired oxide single crystal is continuously supplied from the raw material rod to the molten zone during crystal growth. However, according to the present invention, by making the composition of the feed rod different from that of the oxide single crystal to be produced, i.e., by making the content of one of the multiple metal elements contained in the feed rod higher than the content of the first metal element in the desired oxide single crystal, it is possible to obtain a large-diameter oxide single crystal that could not be obtained by the conventional manufacturing method. The reason why a large-diameter oxide single crystal can be obtained is that, as shown in the experimental example described later, by making the feed rod contain a large amount of the first metal element, the first metal element that evaporates during crystal growth by the TSFZ method is compensated for, a highly stable molten zone can be formed, and the problem of contact between the feed rod and the grown single crystal can be avoided.

[0019] The content of the first metal element in the raw material rod is preferably adjusted to an extent that is in excess of the content of the first metal element in the oxide single crystal, depending on the type of oxide to be produced, the simple substance of the most volatile metal element contained in the oxide, the evaporation amount of the oxide, the vapor pressure in the growth atmosphere, and the like. As an example, the composition of the desired oxide single crystal can be a stoichiometric composition. For example, when attempting to obtain a lithium cobalt oxide single crystal having a stoichiometric composition of Li:Co=50:50, it is preferable to make the Li content in the raw material rod in excess of 50 mol%, which is the Li content in the desired oxide single crystal. As an example, in a manufacturing method according to an embodiment of the present invention, the content of the first metal element in the raw material rod is preferably 1 mol% or more in excess of the content of the first metal element in the oxide single crystal, preferably 2 mol% or more in excess, and in some cases, preferably 3 mol% or more in excess. Here, the content of the first metal element in the oxide single crystal indicates the content (mol%) of the first metal element contained in the oxide single crystal when the total of the first metal element, the second metal element, and other metal elements contained in the oxide single crystal is 100 mol%. In addition, the content of the first metal element in the raw material rod indicates the content (mol%) of the first metal element contained in the raw material rod when the total of the first metal element, the second metal element, and other metal elements contained in the raw material rod is 100 mol%.

[0020] Furthermore, if the content of the first metal element is too excessive relative to the content of said first metal element in the oxide single crystal, volatile matter originating from the first metal element from the molten zone increases, and these volatile matter precipitate in the container of the single crystal growth apparatus, and the precipitates may block the light from the heating lamp and / or cause foreign matter to be mixed into the crystal being grown, adversely affecting the efficiency and quality of the crystal growth. Therefore, as an example, the upper limit of the excess content of said first metal element relative to the content of the first metal element in the oxide single crystal is preferably 10 mol% or less, more preferably 8 mol% or less, and in some cases, preferably 4 mol% or less. Depending on the type of oxide to be produced, the content of the first metal element can be, for example, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 6.0, 7.0, 8.0, 9.0, or 10 mol% in excess of the content of the first metal element in the oxide single crystal, and can be within a range between any two of the numerical values ​​exemplified here.

[0021] The oxide single crystal according to one embodiment of the present invention includes a first metal element and a second metal element. Here, the first metal element according to one embodiment of the present invention is preferably an alkali metal element or an alkaline earth metal, more preferably an alkali metal element. The first metal element according to one embodiment of the present invention is more preferably any one of Li, Na, K, Mg, Ca, Sr, and Ba, more preferably Li or Na.

[0022] The second metal element according to an embodiment of the present invention is preferably a transition metal element, specifically Co, Ni, Mn, Fe, or Cr, and is preferably Co, Ni, or Mn.

[0023] The oxide constituting the oxide single crystal according to one embodiment of the present invention is preferably a decomposed melting oxide. Examples of decomposed melting oxides include Li3VO4, LiCoO2, NaCoO2, Li x La (1-x) / 3 NbO3, La 2 / 3-x Li 3x Among these, LiCoO2, NaCoO2, Li x La (1-x) / 3 NbO3, La 2 / 3-x Li 3x TiO3 is preferred, and LiCoO2 is more preferred.

[0024] The oxide constituting the oxide single crystal according to one embodiment of the present invention is preferably an oxide containing Li as the first metal element and Co as the second metal element. The oxide containing Li as the first metal element and Co as the second metal element according to one embodiment of the present invention may further contain a third metal element. Examples of the third metal element include Nb, Ta, Zr, and Ti.

[0025] In the manufacturing method according to one embodiment of the present invention, it is important to form a stable molten zone having an appropriate length between the feed rod and the seed crystal. The length of the molten zone is preferably adjusted according to the diameter of the target single crystal, and / or the diameter of the raw material rod supporting the molten zone, and / or the diameter of the seed crystal. For example, when the diameter of the oxide single crystal to be produced is Dmm, the length of the molten zone can be 0.5Dmm or more, more preferably 0.6Dmm or more, and more preferably 0.7Dmm or more. In addition, it is preferable that the molten zone has a length that can be maintained by surface tension, and the upper limit of the length of the molten zone can be, for example, 1.2Dmm or less, 1.1Dmm or less, or 1.0Dmm or less. The length of the molten zone can be, for example, 0.5D, 0.6D, 0.7D, 0.8D, 0.9D, 1.0D, 1.1D, or 1.2Dmm, and may be within a range between any two of the numerical values ​​exemplified here.

[0026] The length of the molten zone is, for example, preferably 5 mm or more, more preferably 6 mm or more, and even more preferably 7 mm or more. The length of the molten zone may be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15 mm, or may be within a range between any two of the values ​​exemplified here.

[0027] In the present invention, the length of the molten zone means the vertical length of the molten zone, i.e., the length in the direction in which the crystal is grown, or the length in the longitudinal direction of the raw material rod. The length of the molten zone can be measured by taking a photograph of the state near the molten zone during crystal growth and using a scale. By setting the length of the molten zone within a certain numerical range depending on the diameter of the desired single crystal, and / or the diameter of the raw material rod supporting the molten zone, and / or the diameter of the seed crystal, etc., it is possible to more reliably prevent contact between the raw material rod and the single crystal growing on the seed crystal during crystal growth, and a more highly stable molten zone can be used to obtain single crystals with larger diameters and superior quality. The length of the molten zone can be controlled by adjusting the amount of the solvent used, the heating means used when forming the molten zone, and the like.

[0028] The amount of the solvent used in the TSFZ method is preferably adjusted according to the diameter of the target single crystal, and / or the diameter of the raw material rod supporting the molten zone, and / or the diameter of the seed crystal, the length of the molten zone to be formed, etc. For example, when the diameter of the oxide single crystal to be produced is D mm, the amount of the solvent is 0.020D 2 ~0.040D 2 g, preferably 0.023D 2 ~0.031D 2 More preferably, the amount of the solvent is 0.020 D 2 , 0.022D 2 , 0.024D 2 , 0.026D 2 , 0.028D 2 , 0.030D 2 , 0.032D 2 , 0.034D 2 , 0.036D 2 , 0.038D 2 , 0.040D 2 g and may be in the range between any two of the examples given here.

[0029] The amount of the solvent is, for example, preferably 2.0 g or more, more preferably 2.5 g or more, and even more preferably 3.0 g or more. The amount of the solvent may be 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 6.0, 7.0, 8.0, 9.0, or 10 g, or may be within a range between any two of the values ​​exemplified here. By appropriately adjusting the amount of solvent, a molten zone of an appropriate length can be formed according to the diameter of the raw material rod supporting the molten zone, and / or the diameter of the seed crystal, and / or the diameter of the desired single crystal, thereby obtaining a more highly stable molten zone.

[0030] The solvent according to one embodiment of the present invention includes an oxide containing a first metal element and a second metal element. The solvent is preferably of a composition capable of forming a liquid phase at a temperature lower than the melting point of the oxide constituting the target oxide single crystal. In one embodiment of the present invention, a molten zone is formed at a temperature lower than the melting point of the target oxide single crystal, and the molten zone is dissolved in the feed rod molten zone near the solid-liquid interface on the feed rod side, and at the same time, an oxide is precipitated from the molten zone near the solid-liquid interface on the seed crystal side of the molten zone to produce a single crystal. The content of the first metal element in the solvent is preferably higher than the content of the first metal element in the raw material of the target oxide single crystal. The content of the first metal element in the solvent is preferably adjusted according to the type of oxide to be produced, etc., with respect to the content of the first metal element in the raw material. As an example, in the production method according to one embodiment of the present invention, the content of the first metal element in the solvent is preferably 10 mol% or more in excess of the content of the first metal element in the raw material of the oxide single crystal, preferably 20 mol% or more in excess, and in some cases, preferably 30 mol% or more in excess. The upper limit of the content of the first metal element in the solvent can be, for example, 15, 20, 25, 30, 35, or 40 mol% in excess of the content of the first metal element in the raw material of the oxide single crystal, or can be within a range between any two of the numerical values ​​exemplified here.

[0031] FIG. 1 shows a schematic diagram of a crystal growth process by the TSFZ method according to one embodiment of the present invention. In a single crystal manufacturing method by the TSFZ method according to one embodiment of the present invention, a raw material rod 1 is supported at its upper part and set up. A seed crystal 2, which serves as a base for growing a single crystal, is set up on an extension line of the longitudinal direction (vertical direction) of the raw material rod. Before the crystal growth process starts, a solvent is attached to the seed crystal side of the end of the raw material rod. After setting the raw material rod 1 and the seed crystal 2, the solvent is heated by a heating means 3, whereby the solvent dissolves, and further a part of the raw material rod in contact with the solvent dissolves, forming a molten zone 4. A single crystal precipitates on the seed crystal 2 from the formed molten zone 4. During heating, in order to stabilize the crystal growth, it is preferable to rotate the raw material rod and the seed crystal relatively in opposite directions to uniformly heat the molten zone. As an example, the rotation speed of the feed rod can be set to 7 to 17 rpm, and the rotation speed of the seed crystal can be set to 20 to 30 rpm.

[0032] The heating means may include a light source and a condenser. A halogen lamp or the like may be used as the light source. An ellipsoidal mirror (hereinafter, also simply referred to as a mirror) or the like may be used as the condenser. Such heating means can dissolve the solvent by concentrating light from the light source using the condenser. In the manufacturing method according to one embodiment of the present invention, it is preferable to use an inclined mirror type single crystal growth apparatus that can tilt the mirror. FIG. 2 shows a schematic diagram (side view) of an inclined mirror type FZ apparatus. As shown in FIG. 2, the inclined mirror type FZ apparatus can tilt the straight line connecting the halogen lamp light source and the focal point of the mirror at an angle α° with respect to the horizontal direction. As an example, the inclination can be set to a direction in which the light beam faces downward (a direction in which the inclination angle α is formed on the upward side, a direction indicated by an arrow in FIG. 2).

[0033] In a manufacturing method according to one embodiment of the present invention, the mirror tilt angle α is preferably set to 2 to 20°, more preferably set to 5 to 15°, and even more preferably set to 7 to 13°. By adjusting the tilt angle of the mirror, the length of the molten zone can be controlled, and in particular, by keeping it within the above numerical range, a stable molten zone that is more suitable for growing large-diameter single crystals can be formed.

[0034] In the manufacturing method according to one embodiment of the present invention, it is preferable to use a heating means capable of forming a molten zone of 5 mm or more. The length of the molten zone formed by the heating means is also related to the size and shape of the filament of the lamp. As an example, it is preferable to use a lamp in which the size of the filament in the vertical plane perpendicular to the line connecting the light source of the lamp and the focal point of the mirror is 4 mm or more. As for the shape of the lamp filament, for example, a halogen lamp with a flat or cylindrical filament can be used, and it is preferable to use a halogen lamp with a cylindrical filament. Furthermore, it is more preferable to use a halogen lamp with a cylindrical filament whose size in the direction perpendicular to the line connecting the lamp light source and the focal point of the mirror is 4 mm or more. By using the above heating means, a long and stable molten zone can be formed, which is more suitable for growing a large diameter single crystal.

[0035] The atmosphere during crystal growth is preferably an inert gas atmosphere, for example, an argon atmosphere. The pressure can be normal pressure, and for example, the inert gas can be flowed at a flow rate of 0.5 to 5.0 L / min. The crystal growth speed can be, for example, 1 to 10 mm / h. The temperature of the melting zone during crystal growth is preferably kept lower than the melting point of the oxide to be produced. In a production method according to one embodiment of the present invention, the temperature of the melting zone during crystal growth is preferably kept lower than the melting point of the oxide constituting the target oxide single crystal. As an example, the temperature of the melting zone during crystal growth can be 1200° C. or lower.

[0036] The oxide single crystal according to one embodiment of the present invention has a diameter of 10 mm or more and a thickness of 3 mm or more, and the oxide single crystal contains at least Li and Co. The oxide single crystal according to one embodiment of the present invention is preferably a lithium cobalt oxide single crystal. That is, the oxide single crystal according to one embodiment of the present invention preferably has a crystal structure of lithium cobalt oxide. Until now, the production of lithium cobalt oxide single crystals has been studied by the FZ method, the TSFZ method, etc., but it was not possible to obtain single crystals with a diameter of more than 7 mm by the conventional methods. The present inventors have succeeded for the first time in producing large-diameter single crystals with a diameter of 10 mm or more and a thickness of 3 mm or more, which could not be achieved by existing methods, by changing the composition of the raw material rod from the conventional LiCoO2 composition. The oxide single crystal according to one embodiment of the present invention can be obtained by the above-mentioned method for producing an oxide single crystal by the TSFZ method.

[0037] The oxide single crystal according to one embodiment of the present invention has a cylindrical or approximately cylindrical shape, and the thickness (height) direction of the cylinder preferably corresponds to the crystal growth direction and the direction perpendicular to the C-axis of the crystal. The oxide single crystal according to one embodiment of the present invention has a thickness of 3 mm or more. The thickness may be, for example, 3, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 60, 70, 80, 90, or 100 mm, or may be within a range between any two of the values ​​exemplified here.

[0038] The oxide single crystal according to one embodiment of the present invention has a diameter of 10 mm or more, preferably 11 mm or more, more preferably 12 mm or more, and even more preferably 13 mm or more. The diameter may be, for example, 10, 11, 12, 13, 14, or 15 mm, or may be within a range between any two of the numerical values ​​exemplified here.

[0039] The oxide single crystal according to one embodiment of the present invention preferably has no heterophase. Further, the oxide single crystal according to one embodiment of the present invention preferably has a metallic luster on the surface and preferably has no white roughness on the surface. Further, the oxide single crystal according to one embodiment of the present invention preferably has no voids of 10 μm or more in its cross section. The presence or absence of heterophase and the presence or absence of voids can be confirmed by observing the cross section of the oxide single crystal by SEM. As an example, the oxide single crystal according to one embodiment of the present invention is preferably observed at a magnification of 100 times in 5 fields of view and has no heterophase or voids.

[0040] The oxide single crystal containing at least Li and Co according to one embodiment of the present invention can be confirmed to have the crystal structure of lithium cobaltate by X-ray diffraction method. As an example, the lithium cobaltate single crystal according to one embodiment of the present invention is Li x It can be represented by CoO2 (0 < x ≤ 1). Further, as an example, the oxide single crystal according to one embodiment of the present invention can contain a third metal element in addition to Li as the first metal element and Co as the second metal element. Examples of the third metal element include Nb, Ta, Zr, or Ti. When the total of the first metal element, the second metal element, and other metal elements contained in the oxide single crystal according to one embodiment of the present invention is 100 mol%, the content of the third metal element can be 0 to 10 mol%, and preferably 0 to 5 mol%.

[0041] Lithium cobaltate single crystals are regarded as promising as the cathode material substrate of next-generation lithium-ion secondary batteries with low cost and high efficiency. The successful growth of single crystals with a diameter of 10 mm or more contributes to the industrialization and popularization of all-solid-state lithium-ion batteries using lithium cobaltate single crystals. Experimental Examples

[0042] <Preparation of raw material rods> (Preparation of raw material rod F-1) Li2CO3 (made by Rare Metallic Co., Ltd., purity 99.9%) and Co3O4 (made by Rare Metallic Co., Ltd., purity 99.9%) were weighed and mixed to obtain the LiCoO2 composition, i.e., Li:Co=50:50. The mixed powder was heated in air at 750°C for 4 hours to synthesize LiCoO2. The synthesized LiCoO2 powder was molded into a cylindrical shape with a diameter of 10 to 15 mm and a length of about 60 mm, and pressed at a hydrostatic pressure of 300 MPa using a rubber press method to produce a raw material rod compact. The raw material rod thus produced was sintered in oxygen at 1050°C for 8 hours to obtain a raw material rod.

[0043] (Preparation of raw material rods F-2 to F-4) LiCoO2 powder was synthesized in the same manner as in the preparation of the raw material rod F-1. Li2CO3 was added to the synthesized LiCoO2 powder and mixed so that the amount of Li was 2, 3, and 5 mol% excess relative to the LiCoO2 composition. That is, while the composition of the raw material is Li:Co=50:50, Li2CO3 was added to the LiCoO2 powder and mixed so that Li:Co=52:48, 53:47, and 55:45. The obtained mixed powder was molded into a cylindrical shape with a diameter of 10 to 15 mm and a length of about 60 mm, and pressed at a hydrostatic pressure of 300 MPa by a rubber press method to produce a raw material rod molding. The prepared raw material rod was sintered in oxygen at 1050°C for 8 hours to obtain raw material rods F-2, 3, and 4, each of which had an excess of Li of 2, 3, and 5 mol%, respectively.

[0044] <Preparation of Solvent> The LiCoO2 powder synthesized in the preparation of the raw material rod was mixed with Li2CO3 at a ratio of Li:Co=85:15. The resulting mixed powder was molded into a cylindrical shape with a diameter of 10 to 13 mm, and pressed at a hydrostatic pressure of 300 MPa using a rubber press method. The pellets were then cut and used for crystal growth in an unsintered state.

[0045] <Seed crystal preparation> A LiCoO2 single crystal with a diameter of 10 mm was prepared as a seed crystal.

[0046] <Production of oxide single crystals> Using the raw material rod and solvent obtained above, LiCoO2 single crystals were produced. Before starting the crystal growth, the solvent was dissolved in pellets cut into pellets and attached to the tip of the raw material rod. A tilted mirror type four-ellipse infrared heating FZ device (TLFZ-4000-H-VPO manufactured by Crystal Systems) was used for single crystal growth. The growth atmosphere was argon, and argon gas was flowed at a flow rate of 1.5 L / min. The growth orientation was

[0001] , the growth speed was 5 mm / h, and the upper and lower shaft rotation speeds were 12 rpm and 25 rpm in opposite directions, respectively. The mirror tilt angle was 10°. The temperature of the molten zone during crystal growth was set to 1100°C.

[0047] As the heating halogen lamp, a flat-type filament halogen lamp or a cylindrical-type filament halogen lamp was used. The shape of the filament of each halogen lamp is shown in Figure 3. The size of the a) flat-type filament was 7 mm square and 3 mm thick (size in the direction perpendicular to the scale in the photograph). The size of the b) cylindrical-type filament was 9 mm long (size parallel to the scale in the photograph), 4.5 mm in inner diameter, and 5.5 mm in outer diameter (size in the direction perpendicular to the scale in the photograph). Here, the size in the direction perpendicular to the scale in the photograph corresponds to the size of the filament in the direction perpendicular to the line connecting the light source of the lamp and the focal point of the mirror. In other words, the size of the filament in the direction perpendicular to the line connecting the light source of the lamp and the focal point of the mirror was 3 mm for the a) flat-type filament and 5.5 mm for the b) cylindrical-type filament.

[0048] Below, LiCoO2 single crystals were produced by varying the Li content in the raw material rod, the amount of solvent, the type of halogen lamp, etc.

[0049] <Effect of Li content in raw material rod on growth of large-diameter LiCoO2 single crystals by TSFZ method> The excess amount of Li in the feed rod affected the stability of the molten zone. As the diameter of the feed rod increases, the lamp power required for crystal growth also increases, and the amount of Li evaporated from the molten zone also increases. In the conventional growth using a 10 mm feed rod containing the same amount of Li as the LiCoO2 composition, a large amount of Li evaporated, which sometimes made the molten zone unstable, making it impossible to grow single crystals with a diameter of more than 7 mm. In order to compensate for the excess Li evaporation from the molten zone during the growth of large-diameter LiCoO2 single crystals, crystal growth was performed using feed rods F-2, 3, and 4, which contained 2, 3, and 5 mol% excess Li relative to the LiCoO2 composition, respectively.

[0050] Figures 4 and 5 are photographs of 10 mm and 13 mm diameter crystals grown by changing the amount of Li and the amount of solvent in the feed rod using a feed rod with an excess of Li of 2, 3, and 5 mol%, respectively. Here, crystals were grown using a cylindrical filament heating lamp and an inclined mirror type four-ellipse infrared heating FZ device. In order to investigate the effect of the Li content in the feed rod on crystal growth by the TSFZ method, the Li content in the feed rod was changed while other crystal production conditions such as the amount of solvent were kept constant. The crystals with a diameter of 10 mm are shown in Figures 4(a), 4(b), and 5(c), and the crystals with a diameter of 13 mm are shown in Figures 5(a), 4(b), and 5(c). As shown in Figures 4(c) and 5(b), when feed rods with an excess of Li of 2 mol% and 3 mol% were used for the 10 mm and 13 mm diameter feed rods, respectively, LiCoO2 single crystals with excellent appearance and metallic luster were obtained. In contrast, when a feed rod with a high Li content was used, the surface became rough and white crystals appeared on the surface, as shown in Figures 4(a) and 5(a). The reason for the appearance of white crystals was thought to be the deposition of Li2O on the crystal surface during growth. Furthermore, when a feed rod with a low Li content was used, contact between the feed rod and the grown crystal occurred periodically and frequently during the growth of the LiCoO2 crystal, which made the molten zone unstable. As a result, the grown crystal had a rough surface and cracks were observed on the surface, as shown in Figures 4(b) and 5(c). Figure 6 shows SEM images of the inside of the rough surface part and the shiny surface part with metallic luster of the grown crystal. Many voids and heterogeneous phases of cobalt oxide were observed inside the rough surface part, but there were no voids or foreign matter inside the shiny surface part.

[0051] Figure 7 shows the relationship between the excess amount of Li in the feed rod and the required lamp power. The deposition of excess Li2O and the instability of the molten zone were related to the amount of Li evaporation during TSFZ growth. In the experiment, as the lamp power increased, the evaporation of Li from the molten zone was promoted, and the Li component evaporated from the molten zone was deposited on the quartz tube surrounding the crystal growth region. The quartz tube with Li2O deposition hindered efficient heat transfer to the molten zone during crystal growth. As a result, contact between the feed rod and the grown crystal occurred frequently, and the lamp power increased. When growing large-diameter crystals of 10 mm or more by the TSFZ method, the amount of Li component deposited on the quartz tube increased with increasing lamp power and excess Li amount in the feed rod. Therefore, it can be seen that the inclusion of a moderate excess of Li in the feed rod relative to the LiCoO2 composition is an important factor for successful growth of large-diameter single crystals of LiCoO2, and this makes it possible to avoid the problem of contact between the feed rod and the grown crystal during crystal growth by the TSFZ method.

[0052] Figure 8 shows the relationship between the optimum excess Li content in the feed rod, the crystal diameter, and the lamp power required for optimum crystal growth, based on the data in Figure 7. This relationship shows that the optimum excess Li content in the feed rod is linear with respect to the diameter of the grown crystal. Furthermore, the required lamp power increased significantly as the crystal diameter increased. In particular, the lamp power required to grow a 13 mm diameter crystal was about twice as much as that required to grow a 7 mm diameter crystal. Therefore, using a feed rod with a small amount of Li2O added to the LiCoO2 composition is particularly effective in stabilizing the molten zone in crystal growth with a diameter of more than 7 mm.

[0053] <Effect of the amount of solvent on the growth of large-diameter LiCoO2 single crystals by the TSFZ method> The amount of solvent also affects the stability of the molten zone and the quality of the resulting crystals in the large-diameter LiCoO2 single crystal growth by the TSFZ method. As shown in Figures 4(c) and 5(b), the optimal amounts of solvent in this experiment for crystal growth with diameters of 10 mm and 13 mm were 2.5 g and 4.9 g, respectively. As shown in Figures 4(d) and 5(d), when the amount of solvent was larger than the optimal amount, the molten zone became longer, the melt was more likely to drip, the melt solidified slightly on the crystal surface, and the crystal surface became rough. The relationship between the optimal amount of solvent and the crystal diameter is shown in Figure 9. The optimal amount of solvent has a linear relationship with the square of the crystal diameter. If the length of the molten zone corresponds to the shape and size of the lamp filament, the volume of the molten zone is proportional to the square of the crystal diameter. Therefore, this result is consistent with the consideration from a geometrical point of view. This also means that the amount of solvent can be estimated from this linear relationship to grow LiCoO2 single crystals with larger diameters.

[0054] <Effect of heating method on growth of large-diameter LiCoO2 single crystals by the TSFZ method> Figure 10 shows a photograph of the molten zone during TSFZ growth of a LiCoO2 single crystal with a diameter of 10 mm using an inclined mirror type image furnace. In the two photographs in Figure 10, different filament types were used as heating lamps. Figure 10(a) shows a photograph of the molten zone when a flat-type filament lamp shown in Figure 3(a) was used, and Figure 10(b) shows a photograph of the molten zone when a cylindrical-type filament lamp shown in Figure 3(b) was used. When a flat-type filament lamp was used, the length of the molten zone was 6 mm, which was shorter than the diameter of the feed rod. This is because the heating area formed by the flat-type filament is small. As a result, the feed rod and the grown crystal periodically came into contact with each other because the gap between the feed rod and the grown crystal was insufficient. On the other hand, as shown in Figure 10(b), the length of the molten zone when a cylindrical-type filament lamp was used was 8 mm, which was 2 mm longer than when a flat-type filament lamp was used. As a result, in the crystal growth using a cylindrical-type filament lamp, the gap between the feed rod and the grown crystal was sufficient, and a highly stable molten zone was obtained.

[0055] It was found that the heated area is significantly related to the size and shape of the filament, and the focusing conditions of the heat lamp filament are related to the stability of the molten zone during the growth test. Figure 11 shows a schematic image of the focused light of flat-type and cylindrical-type filament lamps with a crystal diameter of 10 mm and a mirror tilt angle of 10°. When a flat-type filament lamp with a thickness of 3 mm and a width of 7 mm is used, the high focused light area is narrower and shorter than that of a cylindrical-type filament lamp with an outer diameter of 5.5 mm and a length of 9 mm. A narrow and short focused light system may be effective for growing crystals with small diameters, but contact between the raw material rod and the grown crystal may easily occur. As shown in (b) of Figure 11, in the cylindrical-type filament lamp, the temperature around the coiled filament is higher than that of the center, so the focused light from the cylindrical-type filament is also irradiated near the solid-liquid interface. Therefore, in the case of the cylindrical-type filament lamp, the high focused area is wider and longer. Due to the high efficiency of the cylindrical-type filament, a stable molten zone is formed, which can avoid the above-mentioned contact problem. [Explanation of symbols]

[0056] 1 raw material rod 2 seed crystals 3 Heating means 4. Melting Zone

Claims

1. A method for producing an oxide single crystal by a moving solvent floating zone melting method, comprising the steps of: A molten zone containing a solvent having a composition different from that of the feed rod is formed between the feed rod and the seed crystal, growing the oxide single crystal on the seed crystal; The oxide single crystal contains at least a first metal element and a second metal element, The raw material rod contains at least the first metal element and the second metal element, The first metal element in the raw material rod has a higher evaporation rate than the second metal element at a temperature at which the raw material rod melts, The content of the first metal element in the raw material rod is greater than the content of the first metal element in the oxide single crystal, The content of the first metal element in the raw material rod is an excess rate of 4 mol% or less with respect to the content of the first metal element in the oxide single crystal; The content of the first metal element in the solvent is greater than the content of the first metal element in the raw material rod; A method for producing oxide single crystals.

2. The method for producing an oxide single crystal according to claim 1 , wherein the first metal element is an alkali metal.

3. 3. The method for producing an oxide single crystal according to claim 1, wherein the oxide constituting the oxide single crystal is a decomposed molten oxide.

4. The method for producing an oxide single crystal according to any one of claims 1 to 3, wherein the length of the molten zone is 5 mm or more.

5. The method for producing an oxide single crystal according to any one of claims 1 to 4, wherein the amount of the solvent is 2.0 g or more.

6. The method for producing an oxide single crystal according to any one of claims 1 to 5, wherein the content of the first metal element in the solvent is higher than the content of the first metal element in the raw material.

7. An oxide single crystal having a diameter of 10 mm or more and a thickness of 3 mm or more, The oxide constituting the oxide single crystal is a decomposed molten oxide, The oxide single crystal contains at least Li and Co.

8. An oxide single crystal having a diameter of 10 mm or more and a thickness of 3 mm or more, The oxide constituting the oxide single crystal is a decomposed molten oxide, The oxide single crystal contains at least Li and Co, Further, it contains a third metal element other than Li and Co, The oxide single crystal has a content of the third metal element of 0 to 10 mol % when the total content of Li, Co and other metal elements contained in the oxide single crystal is 100 mol %.

Citation Information

Patent Citations

  • Bulky single crystal of alkali cobalt oxide and its manufacturing method

    JP2004189537A

  • Floating zone meting method, and device using the same

    JP2016147800A

  • Oxide semiconductor single crystal, method for manufacturing the same, transparent conductive material and transparent conductive substrate

    JP2018177621A

  • Ferroelectric single crystal, surface acoustic filter making use of the same and process for producing the filter

    WO2007046176A1

  • Lithium-containing oxide crystal, battery and method for producing lithium-containing oxide crystal

    WO2020189705A1